Gambling problems among United Kingdom armed forces veterans: Associations with gambling motivation and posttraumatic stress disorder. Issue 1 (2nd January 2023) - Dighton, Glen; Wood, Katie; Armour, Cherie; Fossey, Matt; Hogan, Lee; Kitchiner, Neil; Larcombe, Justyn; Rogers, Robert D.; Dymond, Simon
ABSTRACT: Military service, mental health, and gambling activities and motivations as predictors of problem gambling in a sample of UK AF veterans. Age-and-gender matched veterans ( n = 1, 037) and non-veterans ( n = 1, 148) completed an online survey of problem gambling, gambling motivation, mental health (depression and anxiety), and posttraumatic stress disorder (PTSD). Past year problem gambling rates were higher in veterans compared to non-veterans. Veteran status predicted increased problem gambling risk. The relationship between problem gambling and gambling to cope with distress was significantly stronger among veterans. Veterans experiencing PTSD and complex PTSD (C-PTSD) were at increased risk of problem gambling. Overall, the present, findings contribute further international evidence that veterans are a population vulnerable to problem gambling. Veterans with PTSD or C-PTSD are most at-risk and may engage in problematic gambling to escape/avoid distress. Routine screening for gambling problems should be undertaken with current and former military personnel, and further research is needed on the interplay between gambling motivation and veterans' mental health.